New Sheriff in (Down)Town?: Business Improvement Areas and the Regulation of Public Spaces: A Case Study of Seattle, Washington - (:unkn) unknown (My University, 2014)
This study examines Business Improvement Areas (BIAs) in Seattle, WA. While the literature on BIAs continues to grow, interestingly, very few studies have been performed on BIAs in west coast cities, as the mass preponderance of the BIA literature body within the United States has focused on east coast cities. Thus, the first purpose of this study is to provide a comparative analysis of Seattle BIAs. This analysis describes the formation, organizational structure, geographic size, budget size, and service programming of each BIA in Seattle. In addition, this thesis also briefly assesses the accountability, the democratic nature, and the potential of BIAs in Seattle to engender or exacerbate inequalities within the urban landscape. The second purpose of this thesis is to examine Seattle's largest BIA, the Metropolitan Improvement District (MID), and its projects, programming, and partnerships. I argue that that the MID is a significant apparatus in the continued privatization of public spaces and creation of "pseudo-private" spaces in Seattle. My analysis suggests that the MID increasingly has set up and rolled out "innovative" regulatory mechanisms through increasingly complex partnerships with the municipal government to manage downtown public spaces in an effort to remake the city for passive consumption rather than allow for active participation and appropriation. Those outside of achieving this goal are deemed problematic, seen as an anathema to redevelopment scheme and therefore must be regulated or removed. This exclusionary focus limits outside individuals' - more commonly homeless persons - right to the city by truncating their ability to move through and make use of urban public space. In addition, the MID also is focused on regulating demonstrators and other participants engaged in political actions.
Keywords: BIAs; Business Improvement Areas; Neoliberalism; Regulation of Space; Seattle; Social Control